2(4y)-y=-1

Simple and best practice solution for 2(4y)-y=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4y)-y=-1 equation:


Simplifying
2(4y) + -1y = -1

Remove parenthesis around (4y)
2 * 4y + -1y = -1

Multiply 2 * 4
8y + -1y = -1

Combine like terms: 8y + -1y = 7y
7y = -1

Solving
7y = -1

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '7'.
y = -0.1428571429

Simplifying
y = -0.1428571429

See similar equations:

| 8-3=2(x+1) | | B=3/4(21-b) | | (n+7)(11n-2)=18n(2n+1) | | A=21-b | | 4/3(-5.25) | | f(4)=2.0x^2+7.6x^4+5.0 | | f(x)=2.0x^2+7.6x^4+5.0 | | F=5(10)+18 | | 9w+(-31)= | | 11n^2+21n-14=0 | | -9/5x=27 | | q=m*c*changeT | | F=5(4)+18 | | F=5(2)+18 | | X+5a=29+ax-6a | | 2n=-28n-3 | | V=XLT | | 2x-x+112=16x+112 | | 3/e=3/4 | | 5n-6=18 | | 2y-3+y+6=12 | | F=5(3)+11 | | F=5(5)+11 | | 2x+8x+4+x=180 | | 2q+2q-48=180 | | 3d=15d | | F=14(4)+18 | | 2q-26=q+19 | | 9/2*-7/2=47/2 | | 3j-9+13j=-1 | | 4p+64+17p+74=180 | | F=14(2)+18 |

Equations solver categories